Exercise-Induced Pulmonary Edema in a Triathlon. (2nd July 2015) - Yamanashi, Hirotomo; Koyamatsu, Jun; Nobuyoshi, Masaharu; Murase, Kunihiko; Maeda, Takahiro
Abstract : Introduction . Family physicians have more opportunities to attend athletic competitions as medical staff at first-aid centers because of the increasing popularity of endurance sports. Case . A 38-year-old man who participated in a triathlon race experienced difficulty in breathing after swimming and was moved to a first-aid center. His initial oxygen saturation was 82% and a thoracic computed tomography scan showed bilateral ground glass opacity in the peripheral lungs. His diagnosis was noncardiogenic pulmonary edema associated with exercise or swimming: exercise-induced pulmonary edema (EIPE) or swimming-induced pulmonary edema (SIPE). Treatment with furosemide and corticosteroid relieved his symptoms of pulmonary edema. Discussion . Noncardiogenic pulmonary edema associated with endurance sports is not common, but knowledge about EIPE/SIPE or neurogenic pulmonary edema associated with hyponatremia, which is called Ayus-Arieff syndrome, is crucial. Knowledge and caution for possible risk factors, such as exposure to cold water or overhydration, are essential for both medical staff and endurance athletes. Conclusion . To determine the presence of pulmonary edema associated with strenuous exercise, oxygen saturation should be used as a screening tool at a first-aid center. To avoid risks for EIPE/SIPE, knowledge about these diseases is essential for medical staff and for athletes who perform extreme exercise.